Learning Community Management (Kombel) In Improving Student Literacy At SDN 2 Jenggala, Tanjung Sub-District, North Lombok - Mastawan, Ika; Yakin, Nurul; Subki, Subki (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
This study aims to determine how the learning community (Kombel) improves student literacy at SDN 2 Jenggala, Tanjung District. The research is a study with the research subject being the Learning Community (Kombel) at SDN 2 Jenggala. Data collection techniques in this study were carried out by observation, interview, and documentation. The author uses triangulation techniques to analyze the information obtained. Based on data analysis, the results obtained from this study show that the learning community of SDN 2 Jenggala has carried out management principles with planning, program implementation, supervision, and evaluation of activities. This is done by the learning community of SDN 2 Jenggala to improve the quality of learning at SDN 2 Jenggala. The program of the SDN 2 Jenggala learning community in improving student literacy is the existence of a reading corner, reading aloud activities, labeling, Salaman ya (Saturday smooth reading), and one word before going home. It is hoped that this activity can be consistently carried out so that it can be transferred to other schools in the Tanjung sub-district. Keywords: Learning Community, Management, Teacher Empowerment